Conceptual Development of a National Volcanic Hazard Model for New Zealand - Stirling, Mark; Bebbington, Mark; Brenna, Marco; Cronin, Shane; Christophersen, Annemarie; Deligne, Natalia; Hurst, Tony; Jolly, Art; Jolly, Gill; Kennedy, Ben; Kereszturi, Gabor; Lindsay, Jan; et al. (Frontiers in Earth Science, 2017)
We provide a synthesis of a workshop held in February 2016 to define the goals, challenges and next steps for developing a national probabilistic volcanic hazard model for New Zealand. The workshop involved volcanologists, statisticians, and hazards scientists from GNS Science, Massey University, University of Otago, Victoria University of Wellington, University of Auckland, and University of Canterbury. We also outline key activities that will develop the model components, define procedures for periodic update of the model, and effectively articulate the model to end-users and stakeholders. The development of a National Volcanic Hazard Model is a formidable task that will require long-term stability in terms of team effort, collaboration and resources. Development of the model in stages or editions that are modular will make the process a manageable one that progressively incorporates additional volcanic hazards over time, and additional functionalities (e.g. short-term forecasting). The first edition is likely to be limited to updating and incorporating existing ashfall hazard models, with the other hazards associated with lahar, pyroclastic density currents, lava flow, ballistics, debris avalanche, and gases/aerosols being considered in subsequent updates.